2023
DOI: 10.3390/en16031014
|View full text |Cite
|
Sign up to set email alerts
|

Abrasive Technologies with Dry Ice as a Blasting Medium—Review

Abstract: The objective of this work was to present an overview of abrasive technologies with solid carbon dioxide as a blasting medium. These methods can be successfully used for the removal of a wide range of types of industrial pollution. The article covers literature reports in the field of the examined cleaning mechanisms and manufacturing process of dry ice, focusing on the structure and size of the product. Having the correct understanding of these processes is crucial for further technological development. Then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Zhao et al, 2022, indicated that DI blocks were successfully used for the rapid cooling of food products [15]. The article by Dzido et al, 2023, describes numerical studies on the removal of solid deposits on the surface, using the dry ice blasting method, in which external coatings were removed by hitting the surface with DI pellets, which rapidly decompressed while penetrating into gaps between the coating and the substrate [16].…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al, 2022, indicated that DI blocks were successfully used for the rapid cooling of food products [15]. The article by Dzido et al, 2023, describes numerical studies on the removal of solid deposits on the surface, using the dry ice blasting method, in which external coatings were removed by hitting the surface with DI pellets, which rapidly decompressed while penetrating into gaps between the coating and the substrate [16].…”
Section: Introductionmentioning
confidence: 99%
“…This, due to the peculiar properties of DI, significantly affects the possibility of its effective use, e.g., in the cooling process [ 11 ]. It results from the unforced phase transition that the material undergoes, i.e., sublimation under normal conditions [ 12 ]. As a result of DI densification, the external surface area of the material on which the indicated phase transition is occurring is reduced, which directly affects the speed of the material’s sublimation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of this system over other cleaning methods have been studied. Firstly, it provides an eco-sustainable approach by projecting recycled CO 2 , which reduces water consumption and eliminates the need for solvents that damage the environment and health [45]. In addition, it ensures the safety of the surfaces by avoiding abrasion due to the low hardness of the pellets used (2 Mohs) [46] and favours the reduction in air pressure required compared to other mechanical methods [47].…”
mentioning
confidence: 99%